Políticas públicas de educação inclusiva e o papel da Universidade Federal do Tocantins para a formação de professores para o ensino de pessoas com deficiência - Silva, Alliny Kássia da (Universidade Federal do Tocantins, 2015)
The research aimed to investigate the contribution of the Federal University of Tocantins - UFT, Campus of Araguaína, in teacher education in the inclusive perspective of students with disabilities. Inclusion in this research conceived as a right that all people have access to and participation of all the services offered in society without discrimination. In education, this means that the student with any kind of disability have the right to be included in a regular schoolroom and the principal has the right to quality education. Meanwhile, the higher education institutions exert vital role through teacher training courses. The UFT has 69 (sixty-nine) undergraduate courses, of which 42 (forty-two) are degrees. With a total of 24 (twenty four) undergraduate courses, our research locus was the Campus of Araguaína, which in turn has the highest initial training of teacher supply in the State of Tocantins. In the analysis of pedagogical projects of undergraduate courses Campus Araguaína, we found that all courses proffer the course of pounds as a compulsory subject, however only the Letters of course offers other compulsory subjects specific to the education of people with disabilities in the classroom regular. We also acknowledge that only the pedagogical projects of the courses History, Physics and Chemistry, focused elective courses do not provide for the inclusion of students with disabilities. By applying a questionnaire with open and closed questions and sent via internet, we found that the Campus of Araguaína / UFT, though, the perception of graduates, contribute to the initial training in the inclusive perspective, as it specifically relates to inclusive education people with disabilities, they said they did not feel prepared, noting that initial training is not the only impediment to the lack of preparation, but also the lack of human and material resources without inclusive practices schools, among other difficulties pointed out. The research concluded that there is no manual, a formula to show how "be prepared" as they are contexts of different teachings, however, mean that universities exert vital role in this include the student process with disabilities through the teaching, research and extension.